Pemanfaatan Pestisida Nabati Dari Ekstraksi Daun Pandan Wangi Dan Umbi Bawang Putih - Pretty Nova M H; Elvi Yenie; Shinta Elystia (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
Pest control with botanical pesticides is a relatively safe alternative control for the environment by using plant extracts that contain ingredients of pesticides. The purpose of this research is to make pesticides from plant materials ie fragrant pandan leaves and bulbs of garlic and test the secondary metabolites of maximum yield. This research was conducted by the method of extraction maceration, variations in immersion time is 1, 3, 5, 7, and 9 days, the ratio of material and solvent is 1: 4, after the immersion process is filtered and the filter in the form of the filtrate and separation of secondary metabolites by rotary evaporator, and then testing the secondary metabolites. The results of the study of secondary metabolites that have been successfully tested by the method of phytochemicals which include alkaloids, flavonoids, saponins, tannins, and sulfur.Keywords: Botanical pesticides, Pandanus amaryllifolius Roxb, garlic bulbs, extraction